(untitled) (Journal of Medical & Health Sciences Review, 2025)
UTIs, bacteremia, multidrug-resistant pneumonia, and other systemic infections are frequently caused by Klebsiella pneumoniae. In blood cultures from patients with sepsis, K. pneumoniae is the third most often found pathogen. It can cause serious epidemic and endemic nosocomial infections that can spread quickly across the population. Because of the emergence of antibiotic resistance, treating K. pneumoniae infections with antibiotics is becoming more difficult, necessitating the development of a novel alternative approach. A kind of virus called a bacteriophage was once employed to cure human illnesses caused on by a variety of bacteria. With an estimated 1031 particles, bacteriophages are the most common biological entity on Earth. They invade bacterial cells as required intracellular parasites. They can multiply and lyse bacterial cells, and they have a high host specificity. Sewage samples were taken from hospital trash, while clinical samples of K. pneumoniae were obtained from the Khyber Teaching Hospital in Peshawar. Two new native bacteriophages against K. pneumoniae strain kp9 were identified and described during this study; they were assigned the scientific names KPP1 and. Since KPP2 was able to lyse four out of eight but was unable to infect bacteria from other species, and KPP1 was able to lyse 3 out of 8 distinct K. pneumoniae clinical isolates, it was determined that both of these phages had a particular host range for K. pneumoniae. The separated phages demonstrated viability at pH values between 3 and 9 and up to 50°C. KPP1 prevented bacterial growth for 18 hours, but KPP2 demonstrated superior bacterial reduction capabilities by preventing and reducing the initial bacterial inoculum count during 24 hours of observation. Both KPP2 and KPP1 may be viable options for treating K. pneumonia, given their superior bacterial growth reduction, phage titer, pH, thermal stability, and host range. Future genetic, physiological, and clinical studies are required to fully characterize these two phages (KPP1 and KPP2).